PENGEMBANGAN METODE LEAN MANUFACTURE UNTUK INVESTIGASI PROSES PRODUKSI HC (HARD COVER) FOLIO DENGAN MENGGUNAKAN VALUE STREAM MAPPING - Muharom Muharom; Sudjito Soeparman; Yudy Surya Irawan (Journal of Engineering and Management in Industrial System, 2013)
A paper company produces many kind of papers where notebooks are its main products. The production approach is make to order. At the completion of the production processes indicates delays due to long lead times. Long lead time of production reduces the company's flexibility and speed of response to customers. The company should shorten the lead time. Shortening lead time, the speed customer response will be faster, the productivity will be increasing and utilization of production resources will more effective. This study propose the use of Value Stream Mapping (VSM) method to overcome it. VSM will identify wastes that can be eliminated, so the company can reduce production costs, meet customer demand, and also increase the company's revenue and market share. The observation identifies wastes in the HC Folio production processes, such as waiting, transportation and unnecessary inventory. Based on the significant wastes, it proposes some improvements to repair the transportation and waiting wastes. To handle work in process parts, the study recommends to implement of rails and trains. It will reduce production time that decreases from 66,828 hours 49 minutes 48 seconds to 30,938 hour 56 minutes 24 seconds.